2023
DOI: 10.3390/antibiotics12091464
|View full text |Cite
|
Sign up to set email alerts
|

ICU-Acquired Colonization and Infection Related to Multidrug-Resistant Bacteria in COVID-19 Patients: A Narrative Review

Alexandre Gaudet,
Louis Kreitmann,
Saad Nseir

Abstract: A large proportion of ICU-acquired infections are related to multidrug-resistant bacteria (MDR). Infections caused by these bacteria are associated with increased mortality, and prolonged duration of mechanical ventilation and ICU stay. The aim of this narrative review is to report on the association between COVID-19 and ICU-acquired colonization or infection related to MDR bacteria. Although a huge amount of literature is available on COVID-19 and MDR bacteria, only a few clinical trials have properly evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In their narrative review, Gaudet et al reported that critically ill COVID-19 patients presented with a greater incidence of HAIs with MDR isolates in the ICU. These authors highlighted several pathophysiological factors that could explain these findings, including COVID-19-mediated post-aggressive immunoparalysis; exposure to antibiotics, steroids, and other immunomodulating agents; a longer ICU stay; exposure to invasive devices; and organizational constraints triggered by the pandemic [29]. During the first waves of the COVID-19 pandemic, nurses in the ICU had an excessive workload; this increase in workload was associated with poor quality of care, unfavourable patient safety, and unfavourable infection prevention [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their narrative review, Gaudet et al reported that critically ill COVID-19 patients presented with a greater incidence of HAIs with MDR isolates in the ICU. These authors highlighted several pathophysiological factors that could explain these findings, including COVID-19-mediated post-aggressive immunoparalysis; exposure to antibiotics, steroids, and other immunomodulating agents; a longer ICU stay; exposure to invasive devices; and organizational constraints triggered by the pandemic [29]. During the first waves of the COVID-19 pandemic, nurses in the ICU had an excessive workload; this increase in workload was associated with poor quality of care, unfavourable patient safety, and unfavourable infection prevention [30].…”
Section: Discussionmentioning
confidence: 99%
“…All patients (100%) received oxygenation support during their ICU stay: 22% were treated by extracorporeal membrane oxygenation, and 94% were treated with invasive mechanical ventilation for a median length of 30 days (Q1-Q3: [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The use of prone positioning, corticosteroids, and neuromuscular blockers was prescribed for most patients (86%, 69%, and 61%, respectively).…”
Section: Demographic and Clinical Datamentioning
confidence: 99%
“…In a recent review of published studies on the impact of COVID-19 infection in the incidence of ICU-acquired MDR colonization/infection, the authors concluded that MDR bacterial superinfection or colonization is similar or potentially lower in COVID-19 patients vs. controls [ 16 ]. Therefore, according to our results, the higher mortality rate observed in critically ill COVID-19 patients was associated with higher disease severity, as assessed with the SOFA score, and the higher presence of comorbidities in this population and not with CRGN bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…are common Gram-negative resistant pathogens that account for bacterial superinfections in COVID-19 patients [ 9 , 11 , 14 , 15 ]. However, most previous studies estimating the risk of MDR infections in COVID-19 patients did not include a comparative non-COVID-19 group of patients to counterbalance the contribution of the ICU epidemiology, which is especially necessary in ICUs with a high prevalence of MDR isolates [ 16 ].…”
Section: Introductionmentioning
confidence: 99%